Case report: Levodopa challenge test is important in identifying dopamine-induced freezing of gait in patient with Parkinson’s disease - Xu, Shan-Shan; Zhu, Shi-Guo; Yuan, Cheng-Xiang; Zeng, Guo-Ling; Li, Xiao-Tian; Liu, Rong-Pei; Huang, Shi-Shi; Zhang, Xiong; Wang, Jian-Yong (Frontiers in Human Neuroscience, 2024)
Introduction Freezing of gait (FOG) is a disabling and heterogeneous symptom in patients with Parkinson’s disease (PD). Among them, dopamine-induced FOG is rare and difficult to identify. The treatment of dopamine-induced FOG is complex. Case presentation We herein presented a case of PD patient who complicated with refractory FOG. It was identified as dopamine-induced FOG during levodopa challenge test. Her symptoms were alleviated after we reduced the total equivalent dosage of levodopa. Conclusion Our report emphasizes the importance of levodopa challenge test in identifying different types of FOG, which is very important for further adjusting treatment.